2018
DOI: 10.1007/s11325-018-1684-9
|View full text |Cite
|
Sign up to set email alerts
|

Excessive daytime sleepiness in general hospital nurses: prevalence, correlates, and its association with adverse events

Abstract: EDS was common among this relatively young and healthy nurse population in south China. There were clear associations between EDS and depression, anxiety, insomnia, rotating shift work, and low work-related interest. Furthermore, EDS was an independent risk factor in the occurrence of adverse events (AEs) in our subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 61 publications
1
10
1
2
Order By: Relevance
“…Although no relevant data exists in the literature regarding Greece in order to be able to compare our findings, we are in good agreement with studies performed in nurses in New Zealand (that reported 33.75% of positive ESS) and Sweden (that reported 32.5% of positive ESS with a cut-off of 9 that was different from the one in our study that was 10) [30,31]. Our results were higher than a recent study performed in China that reported 16.1% positive ESS but the cut-off the authors used was 14, therefore these results are not directly comparable with the current study [32]. Another important finding of our study was that the nursing population working in shift status had significant instability in all three main meals of the day as determined by the self-report of participants of meal skipping.…”
Section: Discussioncontrasting
confidence: 99%
“…Although no relevant data exists in the literature regarding Greece in order to be able to compare our findings, we are in good agreement with studies performed in nurses in New Zealand (that reported 33.75% of positive ESS) and Sweden (that reported 32.5% of positive ESS with a cut-off of 9 that was different from the one in our study that was 10) [30,31]. Our results were higher than a recent study performed in China that reported 16.1% positive ESS but the cut-off the authors used was 14, therefore these results are not directly comparable with the current study [32]. Another important finding of our study was that the nursing population working in shift status had significant instability in all three main meals of the day as determined by the self-report of participants of meal skipping.…”
Section: Discussioncontrasting
confidence: 99%
“…For instance, a population-based 4-year cohort study from Taiwan confirmed that relapse insomnia increased the risk of anxiety and depression [38]. Another recent study of a young and healthy nurse population in south China also identified depression as an independent risk factor for excessive daytime sleepiness, with an adjusted odds ratio of 2.24 (95% CI 1.51–3.31) [28]. The results of the current study were consistent with these previous studies, in demonstrating a close association between depression and poor sleep, but not indicating a cause-effect relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This exhaustion was certainly actual of our participants who described accidents or near accidents when traveling home, sleepy after 24-25 hr at work. Excessive sleepiness is a significant factor in numerous life-threatening traffic accidents (Chen et al, 2019). Specifically, there are increased risks of traffic accidents reported at 11.5 times for those who sleep <4 hr in the past 24 hr, compared with just 1.3 times after seven hours of sleep (Lee et al, 2016).…”
Section: Being Exhaustedmentioning
confidence: 99%